Eosinophilic Granulomatosis With Polyangiitis: Dissecting the Pathophysiology - Fagni, Filippo; Bello, Federica; Emmi, Giacomo (Frontiers in Medicine, 2021)
Eosinophilic Granulomatosis with Polyangiitis (EGPA) is a rare multisystemic disease classified both amongst hypereosinophilic disorders and ANCA-associated vasculitis. Vessel inflammation and eosinophilic proliferation are the hallmarks of the disease and main effectors of organ damage. Two distinct disease phenotypes have classically been described according to ANCA-status: the ANCA-negative subset with eosinophil-driven manifestation and the ANCA-positive one with vasculitic manifestations. An analogous dichotomization has also been backed by histological findings and a distinct genetic background. EGPA is typically consider a Th2-mediated disease and blood and tissue eosinophilia represent the cornerstone of diagnosis. Besides, ANCA are known for inducing endothelial injury and vascular inflammation by activating the circulating neutrophils. Thus, the pathogenesis of EGPA seems to be mediated by two coexisting mechanisms. However, the verbatim application of this strict dualism cannot always be translated into routine clinical practice. In the present review we describe the current knowledge on the eosinophilic and ANCA-mediated aspects of EGPA pathogenesis. Finally, we review the rationale of the currently proposed EGPA dichotomy and future research perspectives.